2017
DOI: 10.1007/s12061-017-9236-4
|View full text |Cite
|
Sign up to set email alerts
|

Violence and Local Development in Fortaleza, Brazil: A Spatial Regression Analysis

Abstract: Fortaleza is the fifth largest city of Brazil, and has become the most violent state capital in the last years. In this paper, we investigate whether violent crime rates are associated with the local development of the city. Using an unexplored data source about georeferenced murders and deaths due to bodily injury and theft, we show that violent crime rates exhibit a positive spatial dependence across clusters of census tracts. In other words, small urban areas with high (low) violent crime rates have neighbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 55 publications
2
14
0
Order By: Relevance
“…Fortaleza had an average incidence of 69.4 violent crimes per 100,000 inhabitants in 2015. The high rate of violent crime was associated with low economic development, limited population's access to infrastructure and health services 37 . Another study, also conducted in Fortaleza, reported a concentration of TB cases in insecure regions with low socioeconomic status 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Fortaleza had an average incidence of 69.4 violent crimes per 100,000 inhabitants in 2015. The high rate of violent crime was associated with low economic development, limited population's access to infrastructure and health services 37 . Another study, also conducted in Fortaleza, reported a concentration of TB cases in insecure regions with low socioeconomic status 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Using the approach of Reich et al [51] for finding sample sizes to compare proportions between group, assuming a risk of seroconversion of 0.30 in the control group and 0.2115 in the intervention group (based on relative risk reduction of 29.5%) and an ICC of 0.07, for 80% power, a significance level of 0.05 and 60 individuals per cluster, 32 clusters are required in each arm. An additional two clusters per arm will be added, in the event that a cluster is removed from the study due to violence creating unsafe conditions for field staff [37,52]. To have a sufficiently powered analysis in the case of a 30% attrition rate of participants, 60/0.7 = 86 individuals per cluster per arm are required.…”
Section: Sample Sizementioning
confidence: 99%
“…Spatial approaches are useful both for the analysis and presentation of useful information on various geographic scales. Spatial methods have been used in many studies across different fields and countries, for example, to study crime rates in Brazil [23], prevalence of low birth weight in Georgia, USA [24], regional distribution of educational attainment in Western Europe [25], adult in-migration patterns in North Carolina, USA [26], differences in secondary school education achievement in Australia [27], distribution and drivers of forest fires in Portugal [28], and for identification and pattern analysis of health care hot spots in Taiwan [29], among many others. In Africa, spatial analysis has been used to examine the link between shifting population trends and climate change revealing hotspots of vulnerability to climate change impacts in central, southern and East Africa [30].…”
Section: Spatial Approaches In Energy Studiesmentioning
confidence: 99%